Bridging the Gap between Differentiated Instruction and Second Language Acquisition among University Students - Malik, Zulfikri; Munir, Ahmad; Lestari, Lies Amin (Prodi Pendidikan Bahasa Inggris, FPBS, Universitas PGRI Semarang, 2025)
Second Language Acquisition (SLA) has drawn considerable attention from researchers and educators seeking effective strategies to enhance language learning. One such approach that has gained traction is differentiated instruction which may be effective in enhancing students' second language acquisition process. To address this, a qualitative case study was conducted to examine the impact of differentiated instruction on students' second language (L2) acquisition. The study involved 15 participants who had undergone an English-intensive program at the university level. Data were collected through online open-ended questionnaires designed to capture cognitive, affective, and conative impacts. The findings reveal that differentiated instruction aligned with students' interests and abilities significantly enhances students' understanding, motivation, and active learning behaviors in their second language acquisition process. However, the study also identified challenges, including difficulties with independent acquisition and intrinsic motivation barriers. Future research should explore the long-term impacts of this research and develop strategies to address the identified challenges, ensuring a broader impact on student second language acquisition.